Heterogeneous clinical spectrum of DNAJC12-deficient hyperphenylalaninemia: from attention deficit to severe dystonia and intellectual disability - Spronsen, F. J. van; Himmelreich, Nastassja; Rüfenacht, Véronique; Shen, Nan; Vliet, Danique van; Al-Owain, Mohammed; Ramzan, Khushnooda; Alkhalifi, Salwa M.; Lunsing, Roelineke J.; Heiner-Fokkema, Rebecca M.; Rassi, Anahita; Gemperle-Britschgi, Corinne; et al. (Journal of medical genetics, 2018)
Background Autosomal recessive mutations in DNAJC12, encoding a cochaperone of HSP70 with hitherto unknown function, were recently described to lead to hyperphenylalaninemia, central monoamine neurotransmitter (dopamine and serotonin) deficiency, dystonia and intellectual disability in six subjects affected by homozygous variants. - Objective Patients exhibiting hyperphenylalaninemia in whom deficiencies in hepatic phenylalanine hydroxylase and tetrahydrobiopterin cofactor metabolism had been excluded were subsequently analysed for DNAJC12 variants. - Methods To analyse DNAJC12, genomic DNA from peripheral blood (Sanger sequencing), as well as quantitative messenger RNA (Real Time Quantitative Polymerase Chain Reaction (RT-qPCR)) and protein expression (Western blot) from primary skin fibroblasts were performed. - Results We describe five additional patients from three unrelated families with homozygosity/compound heterozygosity in DNAJC12 with three novel variants: c.85delC/p.Gln29Lysfs*38, c.596G>T/p.*199Leuext*42 and c.214C>T/p.(Arg72*). In contrast to previously reported DNAJC12-deficient patients, all five cases showed a very mild neurological phenotype. In two subjects, cerebrospinal fluid and primary skin fibroblasts were analysed showing similarly low 5-hydroxyindolacetic acid and homovanillic acid concentrations but more reduced expressions of mRNA and DNAJC12 compared with previously described patients. All patients responded to tetrahydrobiopterin challenge by lowering blood phenylalanine levels. - Conclusions DNAJC12 deficiency appears to result in a more heterogeneous neurological phenotype than originally described. While early identification and institution of treatment with tetrahydrobiopterin and neurotransmitter precursors is crucial to ensure optimal neurological outcome in DNAJC12-deficient patients with a severe phenotype, optimal treatment for patients with a milder phenotype remains to be defined.